Optimal design of passive power filters using genetic algorithm - Muhammd, Faiz (2015)
Recent advances in the field of power electronic technology and growing and wide-spread uses of nonlinear loads are responsible for the generation of the harmonics in the power system; this significantly degrades the power quality. One of the most common methods to reduce harmonic distortion is to use the passive filters. The objective of this research is to develop a system with three-phase uncontrolled rectifier for harmonic analysis and to design an optimal harmonic passive filter. Since the applications of “artificial intelligence” has been increased to find the practical solutions for the recent developments in engineering and technology. Therefore, it has been decided to apply genetic algorithm for the optimization of passive filter design. In order to fulfil the objectives, optimum passive power filters are designed using MATLAB software. The optimal filter improves the system performance by reducing the harmonic distortion which complies with the standard limits.